Python based Frequency Sampling Technique Algorithm for Hearing Impairment - Mahadik, Yogita S.; Kolte, Mahesh T. (International journal of recent technology and engineering, 2019)
Hearing is taken into account because the most vital senses of humans connects us to the world always and the communication between humans are mostly by speaking and listening. As per World Health Organization, 466 million People at Risk of the hearing impairment across the world. It adversely affects physical, behavioral, and social functions, as well as the general quality of live. The most task of the hearing aid is used to by selection amplify the audio sounds such the processed sound can be audible for hearing impairment. In this work, frequency sampling method is used to design a filter for hearing impairment. The proposed algorithm is implemented using python programming. The sound is categorized into two ways vowels and consonants. Vowels have low frequencies that means high pitch and are easier to hear. Consonants have higher frequencies and harder to hear. The changes in formants and pitch is observed which would be useful speech for hearing impaired.